2021
DOI: 10.3390/atmos12020210
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Primary Productivity and Phytoplankton Community to the Atmospheric Nutrient Deposition in the East China Sea

Abstract: Atmospheric deposition of nutrients to the surface seawater may significantly affect marine phytoplankton growth. Two in situ bioassay experiments were performed in the East China Sea (ECS) by adding nutrients (N, P, and Si) and atmospheric aerosols into the surface seawater. Chlorophyll a (Chl a) concentrations were largely enhanced by simultaneous input of N and P with the maximal increase of 0.68–0.78 μg Chl a per μmol N addition. This Chl a increment was significantly lower (0.19–0.47 μg) in aerosol treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 87 publications
1
1
0
Order By: Relevance
“…especially ammonium and phosphate discharged into the lagoon from drains (stations 4, 7, 11, and 12); furthermore, the excessive nutrient supply of N relative to P may influence dominant phytoplankton classes (Ma et al, 2021). This finding was consistent with those of Zingstra (2013), who showed that the increase in phytoplankton is related to a high amount of effluents discharged into the lagoon.…”
Section: Phytoplankton Composition and Abundancesupporting
confidence: 84%
“…especially ammonium and phosphate discharged into the lagoon from drains (stations 4, 7, 11, and 12); furthermore, the excessive nutrient supply of N relative to P may influence dominant phytoplankton classes (Ma et al, 2021). This finding was consistent with those of Zingstra (2013), who showed that the increase in phytoplankton is related to a high amount of effluents discharged into the lagoon.…”
Section: Phytoplankton Composition and Abundancesupporting
confidence: 84%
“…3 ) indicated that diatoms were affected by COD, BOD, and TS, whereas the presence of blue-green algae was highly affected by pH, as they tend to grow better at a high pH. Through photosynthesis and respiration, there is a relationship between algal development and oxygen levels (DO, COD, and BOD) in the aquatic ecosystem (Ma et al, 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%